Eva of the Farm - Calhoun, Dia (Atheneum Books for Young Readers, 2012)
Twelve-year-old Eva writes beautiful poems on the farm in Washington State that her family has owned for generations, but when money runs out and then her baby brother gets sick, the family faces foreclosure and the way of life she loves is threatened.